CinQASE E-module: Its Effectiveness to Improve Senior High School Students’ Physics Learning Outcomes - M Hunaidah; Erniwati Erniwati; Muhamad Arif Mahdiannur (Jurnal Penelitian Pendidikan IPA, 2022)
One of the many digital technologies to actualize the digital learning environment is to provide e-modules based on collaboration in questioning, analyzing, synthesizing, and evaluating (CinQASE) learning model. The main purpose of this study was to analyze the effectiveness of the CinQASE e-module to improve students' learning outcomes in 10th grade in several Senior High Schools in Kendari, Southeast Sulawesi Province. This study implemented design-based research with a three-group pretest-posttest design. 85 students in the 10th grade participated in this study. The research subjects consist of three classes. Each class will use the CinQASE e-modules with different concepts. These concepts were Work and Energy, Momentum and Impulse, and Circular Motion. The differences in learning outcomes will be tested and evaluated based on the t-test. The results of the data analysis showed the normalized gain in the medium category, and the differences in learning outcomes showed a significance level (0.000) < 0.05 for all classes. Consistently implementing the CinQASE e-module can improve physics learning outcomes for all class groups with Sig. (0.161) > 5%. Hence, the CinQASE e-module had the potential to be used in physics classrooms and improve senior high school students’ learning outcomes